Automatização de configuração de múltiplos switches em uma rede utilizando uma SBC com gerência remota e sistema web - Daniel, André Luís Maldonado (2022)
The present work aims to present the development of a group of embedded systems software for the remote management of switches. The system was developed aiming at low cost when using a Raspberry Pi Model B +. For the development of the system, the web interface of a TP-Link TL-SG108E switch was studied. After studying the switch interface, the project was divided into three parts: front-end, back-end and database. The front-end, or web interface, was developed using the VueJs JavaScript framework and the Nuxt framework. The back-end, which works as a mediator between the database and the web interface, in addition to being responsible for accessing and configuring switches on the local network, was developed using the NodeJs JavaScript execution environment, the Application Programming Interface (API) Puppeter and the NestJs framework. The database used in the development of the project was MYSQL.